The interventional effect of Polygonatum cyrtonema Hua polysaccharide on atherosclerosis in mice of different sexes - Anjun Guo; Xueying Li; Lihua Pan; Qiangming Li; Jianping Luo; Xueqiang Zha (Food Science and Human Wellness)
In the present study, we investigated the intervention effects of a purified Polygonatum cyrtonema polysaccharide (PCP) on high-fat diet (HFD)-induced atherosclerosis in male and female LDLr−/− mice. Results showed that HFD caused severe dyslipidemia, atherosclerotic lesions, oxidative damages and inflammation in male and female mice, and these effects seemed to be more pronounced in males than in females. However, the above variations could be dose-dependently reversed by PCP treatment, and the intervention effects on males were greater than those on females. Nuclear factor kappa-B (NF-κB), mitogen-activated protein kinase (MAPKs) and protein kinase B (Akt) are 3 pivotal signaling pathways mediating the development of atherosclerosis. Consistently, PCP was also found to significantly decrease the phosphorylation of p65, p38, extracellular-regulated kinase 1/2 (ERK1/2) and Akt, and increase the protein expression of inhibitor of NF-κB (IκB) in the aortas of male and female mice induced by HFD. Taken together, these findings indicated that PCP could be effective for the prevention of atherosclerosis, and the intervention effect of PCP on male mice was more obvious than that of female mice.